Influenza Vaccine Effectiveness in Inpatient and Outpatient Settings in the United States, 2015–2018. (9th April 2020) - Tenforde, Mark W; Chung, Jessie; Smith, Emily R; Talbot, H Keipp; Trabue, Christopher H; Zimmerman, Richard K; Silveira, Fernanda P; Gaglani, Manjusha; Murthy, Kempapura; Monto, Arnold S; Martin, Emily T; McLean, Huong Q; et al.
Abstract: Background: Demonstration of influenza vaccine effectiveness (VE) against hospitalized illness in addition to milder outpatient illness may strengthen vaccination messaging. Our objective was to compare patient characteristics and VE between United States (US) inpatient and outpatient VE networks. Methods: We tested adults with acute respiratory illness (ARI) for influenza within 1 outpatient-based and 1 hospital-based VE network from 2015 through 2018. We compared age, sex, and high-risk conditions. The test-negative design was used to compare vaccination odds in influenza-positive cases vs influenza-negative controls. We estimated VE using logistic regression adjusting for site, age, sex, race/ethnicity, peak influenza activity, time to testing from, season (overall VE), and underlying conditions. VE differences (ΔVE) were assessed with 95% confidence intervals (CIs) determined through bootstrapping with significance defined as excluding the null. Results: The networks enrolled 14 573 (4144 influenza-positive) outpatients and 6769 (1452 influenza-positive) inpatients. Inpatients were older (median, 62 years vs 49 years) and had more high-risk conditions (median, 4 vs 1). Overall VE across seasons was 31% (95% CI, 26%–37%) among outpatients and 36% (95% CI, 27%–44%) among inpatients. Strain-specific VE (95% CI) among outpatients vs inpatients was 37% (25%–47%) vs 53% (37%–64%) against H1N1pdm09; 19% (9%–27%) vs 23% (8%–35%) against H3N2; and 46% (38%–53%) vs 46% (31%–58%) against B viruses. ΔVE was not significant for any comparison across all sites. Conclusions: Inpatients and outpatients with ARI represent distinct populations. Despite comparatively poor health among inpatients, influenza vaccination was effective in preventing influenza-associated hospitalizations. Abstract : We compared patient characteristics and influenza vaccine effectiveness (VE) between US hospital and outpatient studies, 2015–2018. Despite hospitalized patients being older and having a higher burden of comorbidities, VE estimates were similar, supporting vaccine protection against hospitalizations associated with influenza.